Music as an art - Scruton, Roger (London Bloomsbury Continuum, 2018)
Roger Scruton is a polymath. He has written authoritatively on a huge range of subjects from the environment to wine, from cosmology to the Middle East. He is also an accomplished musician (organ and piano) and a composer of works including an opera and a song cycle. This is Scruton's second major work on music for Bloomsbury--the first being Understanding Music (Continuum, 2009). In this new book he turns again to the meaning of tonality and sound. His abstract, somewhat mystical, argument on these topics includes slashing attacks on Marxist reductionism, the authenticity of Early Music, on rival aestheticians such as Adorno and on sentimentality and cliché in any form.
Part I, Philosophical investigations. When is a tune? ; Music and cognitive science ; Music and the moral life ; Music and the transcendental ; Tonality ; German idealism and the philosophy of music -- Part II, Critical explorations. Franz Schubert and the Quartettsatz ; Rameau the musician ; Britten's dirge ; David Matthews ; Reflections on Deaths in Venice ; Pierre Boulez ; Film music ; The assault on opera ; Nietzsche on Wagner ; The music of the future ; The culture of pop
Includes bibliographical references (pages 245-249) and index 505 0#
Keywords: Music -- Philosophy and aesthetics